Sistem Integrasi Aplikasi Desktop Klinik MCU TKI Pada Medical Center Purwokerto - Lutfi Syafirullah; Hidayat Muhammad Nur; Vadlya Ma’arif (Journal of Innovation Information Technology and Application (JINITA), 2020)
Information technology integration is expected to be able to accommodate the ease and improvement in supporting database platforms through intranet and internet infrastructure. Integration is intended to blend desktop and web database systems. Medical Checkup Purwokerto is a designated place to facilitate the checkup health of the official PJTKI Banyumas Disnaker BNP2TKI. The current system, which is a check-up application, is carried out by prospective Indonesian Workers or Medical checkup units, covering many processes including registration, health checks, types, results, payments and reports. There was a buildup of operational activities Clinical work on a daily basis, by the administrator of the medical record so that management aimed at developing a web-based clinical information system includes the scope of the processed database components, access authorization, and security. The method used is the software development life cycle (SDLC) with the Evolutionary Prototype Model. Results, patient data can be integrated as a whole process flow with a client-server network architecture